The Impact of Spirituality and Spiritually-Oriented Therapeutic Interventions on Schizophrenia Patients - Özge Erduran (Spiritual Psychology and Counseling)
Schizophrenia, with its various aspects that are as yet as unexplainable and which causes those suffering from it to move away from relationships and reality, is a severe psychiatric disorder that usually deteriorates thinking and behavior from an early age. A general definition of schizophrenia has been mentioned for the purpose of this study without describing the types of schizophrenia in detail. The main axis of the study is what role spirituality may have in increasing schizophrenic patients’ well-being, which is the last step in the model for their medical treatment. A lack of deterioration in patients’ consciousness and short-term memory is very important in order for them to be able to understand the therapeutic practices; the study discusses spiritual counseling practices that can be studied with schizophrenic patients who have no problems in these areas. The study evaluates the concept of insight in schizophrenia patients from different perspectives and includes spiritual counseling practices that can be done with schizophrenia patients possessing high levels of insight. The study continues by examining which individual spiritual counseling practices are possible for patients with schizophrenia and presents the example of group counseling over spiritual counseling practices for patients with schizophrenia as well as which counseling practices can be done for schizophrenic patients and their families. The main aim of this study is to present to clinicians, psychologists, and psychological counselors working in the field a general review of the literature on studies that have examined the relationship between schizophrenia and spirituality and to give them ideas into how to integrate spiritual counseling practices into the process while working with schizophrenia patients and their relatives.